O metodzie idealizacji i konkretyzacji w filozofii politycznej liberalizmu - Ciesielski, Mieszko (Studia Europaea Gnesnensia, 2011)
In the article, I introduce the interpretation of selected concepts of liberalist think-ers in the perspective of idealisational theory of science, expounded by Piotr Przybysz in the book entitled “Modele teoretyczne we współczesnej filozofii politycznej liberalizmu (Theoretical models in the contemporary political philosophy of liberalism)”. With this purpose in mind, I characterise the fundamental tenets of idealisation and concretisation methodology and quote the principal argumentation threads of Przy-bysz’s for the sake of a thesis that the method of conceptualisation employed by John Rawls, Robert Nozick, James Buchanan and Gordon Tullock may be defined as idealisa-tion of reality. Moreover, I present an attempt at alternative interpretation of Nozick’s vision of socio-political dynamics in the light of idealisational theory of science.